2021
DOI: 10.1101/2021.01.27.428400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptative Machine Translation between paired Single-Cell Multi-Omics Data

Abstract: Single-cell multi-omics technologies enable profiling of several data-modalities from the same cell. We designed LIBRA, a Neural Network based framework, for learning translations between paired multi-omics profiles into a shared latent space. We demonstrate LIBRA to be state-of-the-art for multi-omics clustering. In addition, LIBRA is more robust with decreasing cell-numbers compared with existing tools. Training LIBRA on paired data-sets, LIBRA predicts multi-omic profiles using only a single data-modality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…paired data, which leverages our ability to dissect and molecularly characterize the intrinsic organization of the bone marrow niche environment. Advances in computational biology have started to develop such tools ( Ashhurst et al., 2021 ; Hao et al., 2021 ; Martinez-de-Morentin et al., 2021 ; Wu et al., 2021 ). Moreover, some validation experiments, such as the use of fluorescent reporters, targeting niche-associated genes, and functional studies will allow us to confirm the identified new molecular markers based on differential gene expression and also the related annotated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…paired data, which leverages our ability to dissect and molecularly characterize the intrinsic organization of the bone marrow niche environment. Advances in computational biology have started to develop such tools ( Ashhurst et al., 2021 ; Hao et al., 2021 ; Martinez-de-Morentin et al., 2021 ; Wu et al., 2021 ). Moreover, some validation experiments, such as the use of fluorescent reporters, targeting niche-associated genes, and functional studies will allow us to confirm the identified new molecular markers based on differential gene expression and also the related annotated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…paired data, which leverages our ability to dissect and molecularly characterize the intrinsic organization of the bone marrow niche environment. Advances in computational biology have started to develop such tools [62][63][64][65] .…”
Section: Discussionmentioning
confidence: 99%
“…Advances in computational biology have started to develop such tools (Ashhurst et al, 2021;Hao et al, 2021;Martinez-de-Morentin et al, 2021;Wu et al, n.d.). Moreover, some validation experiments, such as the use of fluorescent reporters, targeting niche-associated genes and functional studies will allow us to confirm the identified new molecular markers based on differential gene expression and also the related annotated pathways.…”
Section: Discussionmentioning
confidence: 99%